A self-repairing anti-corrosion coating, preparation method and application thereof in magnesium alloy

By forming a self-healing coating on the surface of the magnesium alloy, the silver-containing organic framework material interacts with 2-mercaptobenzimidazole, the problem of insufficient load capacity and binding force of the anti-corrosion coating material of the magnesium alloy is solved, and efficient The self-repair and corrosion-proof effect significantly improves the corrosion resistance and industrial application value of magnesium alloys.

CN116515386BActive Publication Date: 2025-01-03JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310498801.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-01-03
Estimated Expiration
2043-05-06
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal material surface treatment, and provides a self-repairing anti-corrosion coating, a preparation method and its application in magnesium alloy. 2,4,6-triformaldehyde phloroglucinol, aminobenzene, silver nitrate, solvent and catalyst are frozen with liquid nitrogen, filled with nitrogen after vacuuming and then thawed, then frozen with liquid nitrogen, heated and kept warm after vacuuming to carry out Schiff base reaction, then filtered, washed and dried to obtain a silver-containing organic skeleton material, and then the silver-containing organic skeleton material is mixed with 2-mercaptobenzimidazole to obtain an anti-corrosion organic skeleton material, and then the organic skeleton material is evenly dispersed in a polyethersulfone solution to obtain a self-repairing anti-corrosion coating, and the corrosion resistance is better than the prior art. The self-repairing anti-corrosion coating is then coated on the surface of the magnesium alloy, the coating thickness is 10-20μm, the particle size of the organic skeleton material in the coating is: 50-800nm, and the specific surface area is: 100-900m 2 ·g ‑1 , pore size: 1.2~5nm, corrosion current density in sodium chloride solution is 8.2×10 ‑11 ‑9.0×10 ‑9 Acm ‑2 , self-repair time ≤42h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal material surface treatment, and in particular relates to a self-repairing anti-corrosion coating, a preparation method and application thereof to magnesium alloys. Background Art

[0002] In recent years, the new Mg-Al magnesium alloy has attracted much attention at home and abroad due to its excellent strength and plasticity, fast extrusion speed and low cost. However, the second phase in Mg-Al magnesium alloy will cause severe galvanic corrosion, greatly shortening the service life of the alloy. At present, the method to improve the corrosion resistance of Mg-Al magnesium alloy is mainly through the rare earth microalloying strategy, that is, by adding rare earth elements to change the second phase type, refine the grain size, reduce the influence of harmful impurities or improve the stability of the corrosion product film. However, the alloying strategy is difficult to completely hinder the occurrence of corrosion reactions, and conventional surface treatment methods are difficult to overcome the rupture of the film layer, which will lead to more serious galvanic corrosion. Based on this, strengthening coating protection is the best choice to solve the corrosion problem of Mg-Al magnesium alloys. The existing anti-corrosion coating materials for magnesium alloys mainly include composite materials containing components similar to those of the base material. For example, "Anti-corrosion composite coating on the surface of magnesium alloy and its preparation method and application (authorization announcement number: CN113106439B)" discloses that a double-layer hydroxide (LDH) film is pre-grown in situ on a magnesium alloy substrate and then a Zn-G / Ni / Al2O3 coating is cold-sprayed, and finally a Zn-G / Ni / Al2O3 / MgAl-LDH composite coating is obtained on the surface of the magnesium alloy. In addition, the prior art also discloses the use of porous structured materials as carriers to obtain coating materials by filling repair agents / corrosion inhibitors, but there are defects such as small loading capacity, uneven distribution, too fast release rate, and weak repair ability. Therefore, designing a membrane material with a pore size matching the repair agent / corrosion inhibitor is a key technical problem. In addition, the main way for traditional coating materials to combine with repair agents / corrosion inhibitors is physical encapsulation or physical adsorption, which will make the binding ability weaker. Therefore, how to obtain a magnesium alloy anti-corrosion coating material with high loading capacity, uniform distribution, strong bonding and strong repair ability is a technical problem that needs to be solved urgently. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a self-repairing anti-corrosion coating, and its preparation method comprises the following steps:

[0004] (1) Mixing 2,4,6-triformaldehyde phloroglucinol, aminobenzene and silver nitrate in a molar ratio of 2:3:3 to 2:3:8, adding an organic solvent, ultrasonically homogenizing, adding a catalyst acetic acid solution, freezing under liquid nitrogen conditions at -196°C, vacuumizing, filling with nitrogen and thawing, freezing again under liquid nitrogen conditions at -196°C, vacuumizing, and keeping warm at 90 to 130°C for 1 to 7 days, then filtering, washing and drying to obtain a silver-containing organic framework material, wherein the aminobenzene is p-phenylenediamine or diphenylenediamine or 4,4'-diaminoterphenyl, the organic solvent is a mixed solution of mesitylene and dioxane in a volume ratio of 1:2 to 2:1, and the concentration of the acetic acid solution is 3 to 6 mol / L;

[0005] (2) mixing the silver-containing organic framework material obtained in step (1) with a 2-mercaptobenzimidazole acetone solution, stirring at room temperature for 12 to 72 hours, and then filtering, washing, and drying to obtain an anti-corrosion organic framework material, wherein the silver-containing organic framework material is 75 to 99 wt.%, and the 2-mercaptobenzimidazole is 1 to 25 wt.% by weight;

[0006] (3) The anti-corrosion organic skeleton material obtained in step (2) is uniformly dispersed in a polyethersulfone N,N-dimethylformamide solution to obtain a self-repairing anti-corrosion coating, wherein the weight ratio is: polyethersulfone: 90-99.9wt.%, anti-corrosion organic skeleton material: 0.1-10wt.%.

[0007] Furthermore, the particle size of the organic framework material in the self-repairing anti-corrosion coating is 50-800 nm, and the specific surface area is 100-900 m 2 ·g -1 , pore size: 1.2~5nm.

[0008] The present invention also provides an application of a self-repairing anti-corrosion coating in a Mg-Al alloy. The self-repairing anti-corrosion coating is uniformly coated on the surface of the Mg-Al alloy, and then heated and dried to obtain a Mg-Al alloy containing the self-repairing anti-corrosion coating. The coating thickness is 10-20 μm, and the corrosion current density in a sodium chloride solution is 8.2×10 -11 —9.0×10 -9 Acm -2 , and the self-repair time is ≤42h.

[0009] Furthermore, the Mg-Al alloy is a magnesium-aluminum-zinc alloy, a magnesium-aluminum-rare earth alloy, or a magnesium-aluminum-calcium alloy.

[0010] Furthermore, the magnesium-aluminum-calcium system is one of Mg-Al-Ca, Mg-0.8Al-0.5Ca, Mg-3Al-2Ca, Mg-2Al-2Ca, Mg-2Al-Ca or Mg-Al-2Ca.

[0011] Furthermore, the magnesium-aluminum-zinc system is one of Mg-Al-Zn, Mg-3Al-2Zn, Mg-2Al-2Zn, Mg-2Al-Zn or Mg-Al-2Zn.

[0012] Furthermore, the magnesium-aluminum-rare earth system is one of Mg-1Al-0.8Y, Mg-2Al-0.5Y, Mg-2Al-1La, Mg-1Al-0.6Ce or Mg-2Al-1.2Ce-0.1Nd.

[0013] Compared with the current prior art, the present invention has the following characteristics:

[0014] Compared with the physical embedding or physical adsorption of coating materials and repair agents / corrosion inhibitors in the prior art, the present invention obtains a new self-repairing anti-corrosion coating material through the synergistic effects of reaction raw materials, ratios, processes, and the interaction between the coating and the substrate. The addition of the repair agent is omitted in the coating material, and the coating material protects the substrate material from corrosion through both physical and chemical effects. The specific advantages are as follows:

[0015] 1) The anti-corrosion organic framework prepared by the present invention and the self-repairing anti-corrosion coating prepared therefrom are new materials and coatings, wherein the precursor of the anti-corrosion organic framework, the silver-containing organic framework material, is obtained by Schiff base reaction; the self-repairing corrosion-resistant coating is obtained by the interaction of the organic framework material with the corrosion inhibitor; wherein the particle size of the anti-corrosion organic framework material is 50 to 800 nm, and the specific surface area is 100 to 900 m 2 ·g -1 , with evenly distributed nanopores, and the skeleton material contains a large number of Ag, N, O and other groups. The silver ions in the anti-corrosion organic skeleton obtained in this way connect the organic skeleton with the corrosion inhibitor 2-mercaptobenzimidazole in the form of coordination bonds. The organic skeleton material has a large specific surface area and rich functional groups, and can be used as a carrier of the corrosion inhibitor and load the corrosion inhibitor with high capacity; its nanopores are also the transportation channels of the corrosion inhibitor, which can realize the controlled release of the corrosion inhibitor.

[0016] 2) The anti-corrosion organic skeleton material obtained in the present invention has an adjustable pore size of 1.2nm to 5nm. The loading amount and release rate of the corrosion inhibitor for organic skeletons with different pore sizes are different. The present invention can effectively adjust the organic skeleton materials with different pore sizes to adapt to the loading and release of different types of corrosion inhibitors, effectively control the release efficiency of the corrosion inhibitor when the corrosion reaction occurs, and control the anti-corrosion effect by achieving controllable loading and release. At the same time, the specific strong binding sites in the organic skeleton, in which the groups are connected to the corrosion inhibitor through coordination bonds, the coordination bonds formed by the present invention have moderate bond energy, which can effectively avoid the premature release of the corrosion inhibitor causing the failure of the anti-corrosion function, and avoid the failure of the corrosion inhibitor to be released.

[0017] 3) The anti-corrosion coating in the present invention has a self-repairing function, which can not only realize the physical protection function for magnesium alloy and prevent the corrosive medium from contacting the magnesium substrate, but also has a chemical protection function. The organic skeleton material in the repair anti-corrosion coating is loaded with silver ions and organic corrosion inhibitors. Even when the corrosive medium contacts the magnesium substrate to produce magnesium ions by corrosion reaction, the organic corrosion inhibitor can be released from the pores of the organic skeleton and react chemically with the magnesium ions to form a precipitation layer, which is covered on the magnesium substrate as a new coating to complete the self-repair of the coating and prevent further corrosion reactions from occurring; for corrosive media containing halogen ions, the silver ions in the self-repairing anti-corrosion coating can capture the halogen ions and react chemically with them to form a precipitation layer, which is further covered on the surface of the magnesium substrate and prevents the corrosive halogen ions from contacting the magnesium substrate. The dual anti-corrosion effects of magnesium substrate protection and medium treatment are formed.

[0018] 4) The anti-corrosion organic skeleton prepared by the present invention and the self-repairing anti-corrosion coating prepared therefrom have the advantages of acid resistance, alkali resistance, resistance to organic solvents (N,N-dimethylformamide, N,N-dimethylacetamide, toluene, ethanol, tetrahydrofuran, benzene, pentane, hexane, methanol, ether, ethyl acetate, acetone, carbon tetrachloride, etc.) and high temperature resistance. The anti-corrosion organic skeleton in the coating is a pure organic skeleton, which is connected by chemical bonds and is resistant to high temperatures. It can maintain structural stability even at 300°C. Therefore, it can protect the base material without affecting the application of the base material under high temperature environment conditions.

[0019] 5) Compared with existing coatings, the coating of the present invention is thinner and has lower cost, with a thickness of only 10-20 μm. The coating thickness can not only not affect the application of the alloy, but also load dual self-healing substances to make the magnesium alloy coating not only anti-corrosion, but also self-repairing, while capturing and blocking corrosive media such as halogens, thereby having good anti-corrosion and industrial application effects.

[0020] 6) Compared with the existing coating, the anti-corrosion coating material obtained by the present invention not only has a better corrosion resistance effect, but also has a corrosion current density of 8.2×10 -11 —9.0×10 -9 Acm -2 , which is far superior to the corrosion resistance of the coating disclosed in the prior art; in addition, the coating obtained by the present invention has a high self-repairing effect, and the repair time is short, which can be controlled within 42 hours. DETAILED DESCRIPTION

[0021] Example 1

[0022] Taking a Mg-Al-Ca magnesium alloy coating containing 1wt.% of an anti-corrosion organic framework material as an example, the coating thickness is 10-20μm, and the preparation method thereof is as follows:

[0023] (1) After mixing 2,4,6-triformaldehyde phloroglucinol, p-phenylenediamine and silver nitrate in a molar ratio of 2:3:6, a mixed solution of mesitylene and dioxane in a volume ratio of 1:1 was added, and after ultrasonication for 10-15 minutes, a 3 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 5-10 minutes, vacuumized for 2-10 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-10 minutes, vacuumized, and then kept at 120°C for three days to obtain a mixed system 1;

[0024] (2) filtering the mixed system 1 obtained in step (1) to obtain a solid 1, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 2-5 hours, washing 2-5 times, and then drying it at 80-100° C. for 12-24 hours to obtain a silver-containing organic framework material 1 after drying;

[0025] (3) adding the silver-containing organic framework material 1 obtained in step (2) to a 0.5M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic framework material in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 24-36 hours, filtering with suction, washing with acetone for 3-5 times, and drying at 100° C. for 12-24 hours to obtain the anti-corrosion organic framework material 1;

[0026] (4) Add the anti-corrosion organic skeleton material 1 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-repairing anti-corrosion coating material 1, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 1:99, and uniformly coat the self-repairing anti-corrosion coating material 1 on the surface of the Mg-Al-Ca series magnesium alloy, wherein the coating thickness is 10-20 μm, and then dry at 80-100°C for 2-12 hours to obtain a magnesium alloy 1 containing a self-repairing anti-corrosion coating.

[0027] The corrosion current density of the Mg-Al-Ca magnesium alloy 1 containing the self-repairing anti-corrosion coating obtained in step (4) of this embodiment in a 3.5wt.% sodium chloride solution is 6.5×10 -10 Acm -2 , and has self-healing function in sodium chloride solution.

[0028] Example 2

[0029] Taking a Mg-Al-Ca magnesium alloy coating containing 1.2wt.% of an anti-corrosion organic framework material as an example, the coating thickness is 10-20μm, and the preparation method thereof is as follows:

[0030] (1) 2,4,6-triformaldehyde phloroglucinol, p-phenylenediamine and silver nitrate were mixed in a molar ratio of 2:3:6, and then a mixed solution of mesitylene and dioxane in a volume ratio of 2:1 was added, and after ultrasonication for 1-10 minutes, a 3 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 2-5 minutes, vacuumed for 10-15 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 1-5 minutes, and then vacuumed, and then kept at 100°C for four days to obtain a mixed system 2;

[0031] (2) filtering the mixed system 2 obtained in step (1) to obtain a solid 2, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 0.5-2 hours, washing 1-3 times, and then drying it at 100-120° C. for 12-18 hours to obtain a silver-containing organic framework material 2;

[0032] (3) Adding the silver-containing organic skeleton material 2 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 12-24 hours, filtering, washing with acetone for 2-4 times, and drying at 100-120°C for 12-18 hours to obtain the anti-corrosion organic skeleton material 2; (4) Adding the anti-corrosion organic skeleton material 2 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-healing anti-corrosion coating material 2, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 1.2:98.8, and uniformly coating the self-healing anti-corrosion coating material 2 on the surface of the Mg-2Al-Ca magnesium alloy, and then drying at 60-80°C for 2-12 hours to obtain a magnesium alloy 2 containing a self-healing anti-corrosion coating.

[0033] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-2Al-Ca magnesium alloy 2 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 5.4×10-10 A cm -2 , immersed in 0.05M sodium chloride solution, the damaged part completed self-repair within 32 hours.

[0034] Example 3

[0035] Taking a Mg-Al-Ca magnesium alloy coating containing 1wt.% of an anti-corrosion organic framework material as an example, the thickness is 10-20μm, and the preparation method thereof is as follows:

[0036] (1) 2,4,6-triformaldehyde phloroglucinol, p-phenylenediamine and silver nitrate were mixed in a molar ratio of 2:3:3, and then a mixed solution of mesitylene and dioxane in a volume ratio of 1:2 was added, and after ultrasonication for 10-12 minutes, a 6 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen conditions at -196°C for 10-12 minutes, vacuumed for 5-10 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen conditions at -196°C for 10-12 minutes, vacuumed, and then kept warm at 90-100°C for five days to obtain a mixed system 3;

[0037] (2) filtering the mixed system 3 obtained in step (1) to obtain a solid 3, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 2-4 hours, washing 3-5 times, and then drying it at 60-80° C. for 6-12 hours to obtain a silver-containing organic framework material 3;

[0038] (3) Adding the silver-containing organic skeleton material 3 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 3 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 12-24 hours, filtering, washing with acetone for 2-4 times, and drying at 50-60°C for 36-48 hours to obtain an anti-corrosion organic skeleton material 3; (4) Adding the anti-corrosion organic skeleton material 3 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-repairing anti-corrosion coating material 3, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 1:99, and uniformly coating the self-repairing anti-corrosion coating material 3 on the surface of the Mg-Al-Ca magnesium alloy, and then drying at 50-60°C for 24-36 hours to obtain a magnesium alloy 3 containing a self-repairing anti-corrosion coating.

[0039] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-Al-Ca magnesium alloy 3 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 7.8×10 -9 Acm -2 , immersed in 0.05M sodium chloride solution, the damaged part completed self-repair within 42 hours.

[0040] Example 4

[0041] Taking a Mg-Al-Ca magnesium alloy coating containing 1.5wt.% of an anti-corrosion organic framework material as an example, the thickness is 10 microns, and the preparation method thereof is as follows:

[0042] (1) 2,4,6-triformaldehyde phloroglucinol, diphenyl diamine and silver nitrate were mixed in a molar ratio of 2:3:9, and then a mixed solution of mesitylene and dioxane in a volume ratio of 1:1 was added, and after ultrasonication for 12-15 minutes, a 6 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 2-5 minutes, vacuumed for 5-10 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-10 minutes, and then vacuumed, and then kept at 120-140°C for four days to obtain a mixed system 4;

[0043] (2) filtering the mixed system 4 obtained in step (1) to obtain solid 4, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 1-2 hours, washing 2-4 times, and then drying it at 100-120° C. for 4-12 hours to obtain a silver-containing organic framework material 4;

[0044] (3) Adding the silver-containing organic skeleton material 4 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 4 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 36-48 hours, filtering, washing with acetone for 2-4 times, and drying at 80-100°C for 6-12 hours to obtain an anti-corrosion organic skeleton material 4; (4) Adding the anti-corrosion organic skeleton material 4 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-healing anti-corrosion coating material 4, wherein the mass ratio of the anti-corrosion organic skeleton material 4 to the polyethersulfone is 1.5:98.5, and uniformly coating the self-healing anti-corrosion coating material 4 on the surface of the Mg-Al-Ca magnesium alloy, and then drying at 100-110°C for 1-6 hours to obtain a magnesium alloy 4 containing a self-healing anti-corrosion coating.

[0045] The corrosion resistance of the Mg-Al-Ca magnesium alloy self-repairing anti-corrosion coating obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 8.2×10 -11 Acm -2 , immersed in 0.05M sodium chloride solution, the damaged part completed self-repair within 20 hours.

[0046] Example 5

[0047] Taking a Mg-Al-Zn magnesium alloy coating containing 0.8wt.% of an anti-corrosion organic framework material as an example, the thickness is 10 μm, and the preparation method thereof is as follows:

[0048] (1) 2,4,6-triformaldehyde phloroglucinol, diphenyl diamine and silver nitrate were mixed in a molar ratio of 2:3:3, and then a mixed solution of mesitylene and dioxane in a volume ratio of 2:1 was added, and after ultrasonication for 10-15 minutes, a 3 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 4-6 minutes, vacuumed for 3-6 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 10-15 minutes, and then vacuumed, and then kept at 120-130°C for three days to obtain a mixed system 5;

[0049] (2) filtering the mixed system 5 obtained in step (1) to obtain a solid 5, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 2-5 hours, washing 3-6 times, and then drying it at 110-120° C. for 8-10 hours to obtain a silver-containing organic framework material 5;

[0050] (3) Adding the silver-containing organic skeleton material 5 obtained in step (2) to a 0.05M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 5 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 18-24 hours, filtering, washing with acetone for 1-3 times, and drying at 90-110°C for 12-18 hours to obtain an anti-corrosion organic skeleton material 5; (4) Adding the anti-corrosion organic skeleton material 5 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-healing anti-corrosion coating material 5, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 0.8:99.2, and uniformly coating the self-healing anti-corrosion coating material 5 on the surface of the Mg-2Al-2Zn magnesium alloy, and then drying at 80-90°C for 2-4 hours to obtain a magnesium alloy 5 containing a self-healing anti-corrosion coating.

[0051] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-2Al-2Zn magnesium alloy 5 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 9.0×10 -9 Acm -2 , and has self-healing ability in 0.05M sodium chloride solution.

[0052] Example 6

[0053] Taking a Mg-Al-Ca magnesium alloy coating containing 2wt.% of an anti-corrosion organic framework material as an example, the thickness is 10 μm, and the preparation method thereof is as follows:

[0054] (1) 2,4,6-triformaldehyde phloroglucinol, diphenyl diamine and silver nitrate were mixed in a molar ratio of 2:3:7, and then a mixed solution of mesitylene and dioxane in a volume ratio of 1:1 was added, and after ultrasonication for 5-10 minutes, a 6 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 6-8 minutes, vacuumed for 2-5 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-8 minutes, vacuumed, and then kept at 130°C for three days to obtain a mixed system 6;

[0055] (2) filtering the mixed system 6 obtained in step (1) to obtain solid 6, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 0.5-2 hours, washing 2-4 times, and then drying it at 120-130° C. for 6-12 hours to obtain a silver-containing organic framework material 6;

[0056] (3) Adding the silver-containing organic skeleton material 6 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 48-72 hours, filtering, washing with acetone for 2-4 times, and drying at 80-90°C for 12-18 hours to obtain the anti-corrosion organic skeleton material 6; (4) Adding the anti-corrosion organic skeleton material 6 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-healing anti-corrosion coating material 6, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 2:98, and uniformly coating the self-healing anti-corrosion coating material 6 on the surface of the Mg-0.8Al-0.5Ca magnesium alloy, and drying at 80-90°C for 12-18 hours to obtain the magnesium alloy 6 containing the self-healing anti-corrosion coating.

[0057] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-0.8Al-0.5Ca magnesium alloy 6 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 9.5×10 -11 Acm -2 , immersed in 0.05M sodium chloride solution, the damaged part completed self-repair within 22 hours.

[0058] Example 7

[0059] Taking a Mg-Al-Ca magnesium alloy coating containing 0.5wt.% of an anti-corrosion organic framework material as an example, the thickness is 10-20μm, and the preparation method thereof is as follows:

[0060] (1) 2,4,6-triformaldehyde phloroglucinol, 4,4'-diaminoterphenyl and silver nitrate were mixed in a molar ratio of 2:3:6, and then a mixed solution of mesitylene and dioxane in a volume ratio of 2:1 was added, and after ultrasonication for 10-15 minutes, a 3 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 5-8 minutes, vacuumized for 5-8 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-10 minutes, and then vacuumized, and then kept warm at 90-120°C for three days to obtain a mixed system 7;

[0061] (2) filtering the mixed system 7 obtained in step (1) to obtain solid 7, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 2-3 hours, washing 2-3 times, and then drying it at 100° C. for 8-12 hours to obtain a silver-containing organic framework material 7;

[0062] (3) Adding the silver-containing organic skeleton material 7 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 7 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 18-24 hours, filtering, washing with acetone for 1-3 times, and drying at 90-110°C for 10-12 hours to obtain the anti-corrosion organic skeleton material 7; (4) Adding the anti-corrosion organic skeleton material 7 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-healing anti-corrosion coating material 7, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 0.5:99.5, and uniformly coating the self-healing anti-corrosion coating material 7 on the surface of the Mg-3Al-2Ca magnesium alloy, and then drying at 60-80°C for 10-12 hours to obtain a magnesium alloy 7 containing a self-healing anti-corrosion coating.

[0063] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-3Al-2Ca magnesium alloy 7 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 9.4×10 -10 Acm -2 , and has self-healing ability in 0.05M sodium chloride solution.

[0064] Example 8

[0065] Taking the Mg-Al-RE series magnesium alloy coating containing 1.8wt.% of anti-corrosion organic framework material as an example, the thickness is 10-20μm, and the preparation method thereof is as follows:

[0066] (1) 2,4,6-triformaldehyde phloroglucinol, 4,4'-diaminoterphenyl and silver nitrate were mixed in a molar ratio of 2:3:3, and then a mixed solution of mesitylene and dioxane in a volume ratio of 1:1 was added, and after ultrasonication for 1-3 minutes, a 6 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 2-6 minutes, vacuumed for 2-6 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-10 minutes, and then vacuumed, and then kept at 120°C for three days to obtain a mixed system 8;

[0067] (2) filtering the mixed system 8 obtained in step (1) to obtain a solid 8, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 2-3 hours, washing 3-5 times, and then drying it at 100° C. for 10-12 hours to obtain a silver-containing organic framework material 8;

[0068] (3) Adding the silver-containing organic skeleton material 8 obtained in step (2) to a 0.05M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 8 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 12-24 hours, filtering, washing with acetone for 1-3 times, and drying at 110-120°C for 8-12 hours to obtain an anti-corrosion organic skeleton material 8; (4) Adding the anti-corrosion organic skeleton material 8 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-repairing anti-corrosion coating material 8, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 1.8:98.2, and uniformly coating the self-repairing anti-corrosion coating material 8 on the surface of the Mg-1Al-0.6Ce magnesium alloy, and then drying at 70-90°C for 8-12 hours to obtain a magnesium alloy 8 containing a self-repairing anti-corrosion coating.

[0069] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-1Al-0.6Ce magnesium alloy 8 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 2.3×10 -10 A cm -2 , and has self-repairing function in 0.05M sodium chloride solution.

[0070] Example 9

[0071] Taking a Mg-Al-Zn magnesium alloy coating containing 3wt.% of an anti-corrosion organic framework material as an example, the thickness is 10-20μm, and the preparation method thereof is as follows:

[0072] (1) 2,4,6-triformaldehyde phloroglucinol, 4,4'-diaminoterphenyl and silver nitrate were mixed in a molar ratio of 2:3:6 to 2:3:8, and then a mixed solution of mesitylene and dioxane in a volume ratio of 2:1 was added, and after ultrasonication for 1-3 minutes, a 3 mol / L acetic acid solution of a catalyst was added, and then the mixture was frozen under liquid nitrogen at -196°C for 5 minutes, vacuumized for 5 minutes, and then filled with nitrogen to thaw, and then frozen under liquid nitrogen at -196°C for 5-10 minutes, and then vacuumized, and then kept at 110-130°C for three days to obtain a mixed system 9;

[0073] (2) filtering the mixed system 9 obtained in step (1) to obtain a solid 9, washing it with N,N-dimethylformamide, water, and acetone, respectively, each washing time is 0.5-3 hours, washing 3-5 times, and then drying it at 90° C. for 12-18 hours to obtain a silver-containing organic framework material 9;

[0074] (3) Adding the silver-containing organic skeleton material 9 obtained in step (2) to a 0.1M 2-mercaptobenzimidazole acetone solution, wherein the concentration of the silver-containing organic skeleton material 9 in the 2-mercaptobenzimidazole acetone is 0.5 g / L, stirring at room temperature for 6-12 hours, filtering, washing with acetone for 2-3 times, and drying at 100-120°C for 4-8 hours to obtain an anti-corrosion organic skeleton material 9; (4) Adding the anti-corrosion organic skeleton material 9 obtained in step (3) to an N,N-dimethylformamide solution of polyethersulfone to obtain a self-repairing anti-corrosion coating material 9, wherein the mass ratio of the anti-corrosion organic skeleton material to the polyethersulfone is 3:97, and uniformly coating the self-repairing anti-corrosion coating material 9 on the surface of the Mg-3Al-2Zn magnesium alloy, and then drying at 60-80°C for 10-12 hours to obtain a magnesium alloy 9 containing a self-repairing anti-corrosion coating.

[0075] The corrosion resistance of the self-repairing anti-corrosion coating of the Mg-3Al-2Zn magnesium alloy 9 obtained in step (4) of this embodiment is significantly improved, and the corrosion current density in a 3.5wt.% sodium chloride solution is 1.0×10 -9 Acm -2 , immersed in 0.05M sodium chloride solution, the damaged part completed self-repair within 40 hours.

[0076] Compared with existing technologies:

[0077] 1. In the prior art, ASGnedenkov et al. published a paper entitled “Protective properties of inhibitor-containing composite coating on a Mg alloy” in the journal Corrosion Science (Volume 102, 2016). The corrosion inhibitor 8-hydroxyquinoline was added to the micro-arc oxidation layer to prepare an anti-corrosion coating on the surface of MA8 magnesium alloy. The corrosion inhibitor was directly added to the coating, which is physical doping. The corrosion current density is 8.6×10 - 8 Acm -2 The corrosion-resistant organic skeleton material coating of the present invention does not directly add corrosion inhibitors. The organic skeleton material coating can capture corrosive anions to form a precipitation layer through dual repair substances (organic corrosion inhibitor 2-mercaptobenzimidazole and inorganic silver ions), and can also react with magnesium ions to form a passivation layer to complete self-repair. At the same time, by adjusting the pore structure, the release rate of the corrosion inhibitor can be effectively regulated. The corrosion resistance of Example 5 is the lowest among all the examples, and the corrosion current density is 9.0×10 -9 Acm -2 , which is far superior to the corrosion resistance of existing technologies.

[0078] 2. Jialing Chen et al. published a paper titled “Corrosion resistance of a self-healing rose-like MgAl-LDH coating intercalated with aspartic acid on AZ31 Mg alloy” in Progress in Organic Coatings (Volume 136, 2019). Aspartic acid was inserted into Mg / Al layered double hydroxide to prepare layered double hydroxide on the surface of AZ31 magnesium alloy. The corrosion current density of the coating was 5.7×10 -8 Acm -2 The corrosion-resistant organic skeleton material coating of the present invention does not directly add corrosion inhibitors. The organic skeleton material coating can capture corrosive anions to form a precipitation layer through dual repair substances (organic corrosion inhibitor 2-mercaptobenzimidazole and inorganic silver ions), and can also react with magnesium ions to form a passivation layer to complete self-repair. At the same time, by adjusting the pore structure, the release rate of the corrosion inhibitor can be effectively regulated. The corrosion resistance of Example 5 is the lowest among all the examples, and the corrosion current density is 9.0×10 -9 Acm -2 , which is far superior to the corrosion resistance of existing technologies.

[0079] In summary:

[0080] By comparing the examples, the content of organic skeleton material added in Example 4 is not the highest among all the examples, but its corrosion resistance is the best among all the examples, and the self-repairing time of the coating is the shortest; in addition, the base material, organic skeleton material content and structure of Examples 1, 7, 8 and 9 are different, and the corrosion resistance of the coating obtained in the end is also different. In summary: the final corrosion resistance of the magnesium alloy material containing the corrosion-resistant coating obtained by the present invention is determined by the synergistic effect of the reaction raw materials, proportions, processes, and the interaction between the coating material and the base material. In addition, compared with the prior art, the present invention omits the addition of a repair agent while breaking the technical bottleneck of the coating material in the prior art that uses a component similar to the base material, and obtains the following advantages: First, the anti-corrosion organic skeleton prepared by the present invention and the self-repairing anti-corrosion coating obtained therefrom are new materials and coatings, and a self-repairing corrosion-resistant coating is obtained by interacting the organic skeleton material with the corrosion inhibitor; wherein the particle size of the anti-corrosion organic skeleton material is 50 to 800 nm, and the specific surface area is 100 to 900 m 2 ·g -1, with nanopores, and the skeleton material contains a large number of Ag, N, O and other groups. The silver ions in the anti-corrosion organic skeleton thus obtained connect the organic skeleton with the corrosion inhibitor 2-mercaptobenzimidazole in the form of coordination bonds. The organic skeleton material has a large specific surface area and rich functional groups, and can be used as a carrier of the corrosion inhibitor, with a high capacity of loading the corrosion inhibitor; its nanopores are also the transportation channels of the corrosion inhibitor, which can realize the controllable release of the corrosion inhibitor; secondly, the anti-corrosion organic skeleton material obtained in the present invention has an adjustable pore size, the pore size is 1.2nm~5nm, and the loading amount and release rate of the corrosion inhibitor of the organic skeleton with different pore sizes are different. The present invention can effectively adjust the organic skeleton materials with different pore sizes to adapt to the loading and release of different types of corrosion inhibitors, effectively control the release efficiency of the corrosion inhibitor when the corrosion reaction occurs, and control the anti-corrosion effect by realizing the controllable loading and release. At the same time, there are specific strong binding sites in the organic skeleton, in which the groups are connected to the corrosion inhibitor through coordination bonds. The coordination bonds formed by the present invention have moderate bond energy, which can effectively avoid the premature release of the corrosion inhibitor causing the failure of the anti-corrosion function, and at the same time avoid the failure of the corrosion inhibitor to be released and cause the anti-corrosion failure; third, the anti-corrosion coating in the present invention has a self-repairing function, which can not only realize the physical protection function for the magnesium alloy and prevent the corrosive medium from contacting the magnesium matrix; but also has a chemical protection function. The organic skeleton material in the repair anti-corrosion coating is loaded with silver ions and organic corrosion inhibitors. Even when the corrosive medium contacts the magnesium matrix to produce magnesium ions by corrosion reaction, the organic corrosion inhibitor can be released from the pores of the organic skeleton, react chemically with the magnesium ions, generate a precipitation layer, and cover the magnesium matrix as a new coating to complete the self-repair of the coating and prevent further corrosion reactions from occurring; for corrosive media containing halogen ions, the silver ions in the self-repairing anti-corrosion coating can capture the halogen ions and react chemically with them to generate a precipitation layer, which is further covered on the surface of the magnesium matrix and prevents the corrosive halogen ions from contacting the magnesium matrix.The dual anti-corrosion effects of magnesium matrix protection and medium treatment are formed; fourthly, the anti-corrosion organic skeleton prepared by the present invention and the self-repairing anti-corrosion coating prepared therefrom have the advantages of acid resistance, alkali resistance, organic solvent resistance (N,N-dimethylformamide, N,N-dimethylacetamide, toluene, ethanol, tetrahydrofuran, benzene, pentane, hexane, methanol, ether, ethyl acetate, acetone, carbon tetrachloride, etc.) and high temperature resistance, wherein the anti-corrosion organic skeleton in the coating is a pure organic skeleton, connected by chemical bonds, resistant to high temperatures, and can maintain structural stability even at 300°C, so it can protect the matrix material while not affecting the The invention can be applied to the substrate material in any environment; fifthly, compared with the existing coating, the coating of the invention is thinner and has lower cost, with a thickness of only 10-20 μm. The coating thickness can not only not affect the application of the alloy, but also load dual self-repairing substances, so that the magnesium alloy coating can not only prevent corrosion, but also self-repair, and at the same time capture and hinder halogen and other corrosive media, so as to have a good anti-corrosion and industrial application effect; sixthly, compared with the existing coating, the anti-corrosion coating material obtained by the invention can not only play a better corrosion resistance effect, but also has a corrosion current density of 8.2×10 in sodium chloride solution. -11 —9.0×10 -9 Acm -2 , which is far superior to the corrosion resistance of the coating disclosed in the prior art; in addition, the coating obtained by the present invention has a high self-repairing effect, and the repair time is short, which can be controlled within 42 hours.

Claims

1. A self-repairing anti-corrosion coating, characterized in that: Its preparation method comprises the following steps: (1) Mixing 2,4,6-triformaldehyde phloroglucinol, aminobenzene and silver nitrate in a molar ratio of 2:3:3 to 2:3:8, adding an organic solvent, ultrasonically homogenizing, adding a catalyst acetic acid solution, freezing under liquid nitrogen conditions at -196°C, vacuumizing, filling with nitrogen and thawing, freezing again under liquid nitrogen conditions at -196°C, vacuumizing, and keeping warm at 90 to 130°C for 1 to 7 days, then filtering, washing and drying to obtain a silver-containing organic framework material, wherein the aminobenzene is p-phenylenediamine or diphenylenediamine or 4,4'-diaminoterphenyl, the organic solvent is a mixed solution of mesitylene and dioxane in a volume ratio of 1:2 to 2:1, and the concentration of the acetic acid solution is 3 to 6 mol / L; (2) mixing the silver-containing organic framework material obtained in step (1) with a 2-mercaptobenzimidazole acetone solution, stirring at room temperature for 12 to 72 hours, and then filtering, washing, and drying to obtain an anti-corrosion organic framework material, wherein the silver-containing organic framework material is 75 to 99 wt.%, and the 2-mercaptobenzimidazole is 1 to 25 wt.% by weight; (3) The anti-corrosion organic skeleton material obtained in step (2) is uniformly dispersed in an N,N-dimethylformamide solution of polyethersulfone to obtain a self-repairing anti-corrosion coating material, and the self-repairing anti-corrosion coating material is uniformly coated on the surface of the magnesium alloy to obtain a self-repairing anti-corrosion coating, according to the mass ratio: polyethersulfone: 90-99.9wt.%, anti-corrosion organic skeleton material: 0.1-10wt.%.

2. A self-repairing anti-corrosion coating according to claim 1, characterized in that: The particle size of the organic framework material in the self-repairing anti-corrosion coating is 50-800nm, and the specific surface area is 100-900m 2 ·g -1 , pore size: 1.2~5nm.

3. Application of the self-repairing anti-corrosion coating according to claim 1 or 2 on Mg-Al alloys, characterized in that: The self-repairing anti-corrosion coating was uniformly coated on the surface of the Mg-Al alloy, and then heated and dried to obtain a Mg-Al alloy containing the self-repairing anti-corrosion coating. The coating thickness was 10-20 μm, and the corrosion current density in the sodium chloride solution was 8.2×10 -11 —9.0×10 - 9 Acm -2 , and the self-repair time is ≤42h.

4. The application of the self-repairing anti-corrosion coating in Mg-Al alloy according to claim 3 is characterized in that: The Mg-Al alloys are magnesium-aluminum-zinc alloys, magnesium-aluminum-rare earth alloys and magnesium-aluminum-calcium alloys.

5. The application of the self-repairing anti-corrosion coating in Mg-Al alloy according to claim 4 is characterized in that: The magnesium-aluminum-calcium system is one of Mg-Al-Ca, Mg-0.8Al-0.5Ca, Mg-3Al-2Ca, Mg-2Al-2Ca, Mg-2Al-Ca or Mg-Al-2Ca.

6. Application of the self-repairing anti-corrosion coating in Mg-Al alloy according to claim 4, characterized in that: The magnesium-aluminum-zinc system is one of Mg-Al-Zn, Mg-3Al-2Zn, Mg-2Al-2Zn, Mg-2Al-Zn or Mg-Al-2Zn.

7. The application of the self-repairing anti-corrosion coating in Mg-Al alloy according to claim 4 is characterized in that: The magnesium-aluminum-rare earth system is one of Mg-1Al-0.8Y, Mg-2Al-0.5Y, Mg-2Al-1La, Mg-1Al-0.6Ce or Mg-2Al-1.2Ce-0.1Nd.